A Ganoderma-Derived Compound Exerts Inhibitory Effect Through Formyl Peptide Receptor 2 - Wang, Huirong; Peng, Xingrong; Ge, Yunjun; Zhang, Shuo; Wang, Zhenyi; Fan, Yu; Huang, Wei; Qiu, Minghua; Ye, Richard D. (Frontiers in Pharmacology, 2020)
Formyl peptide receptors (FPRs) are G protein-coupled receptors (GPCRs) widely expressed in neutrophils and other phagocytes. FPRs play important roles in host defense, inflammation and the pathogenesis of infectious and inflammatory diseases. Because of these functions, FPRs are potential targets for anti-inflammatory therapies. In order to search for potentially novel anti-inflammatory agents, we examined Ganoderma (Lingzhi), a Chinese medicinal herbs known for its anti-inflammatory effects, and found that compound 18 (C18) derived from Ganoderma cochlear could limit the inflammatory response through FPR-related signaling pathways. Further studies showed that C18 could bind to FPR2 and induce conformation change of the receptor that differed from the conformational change induced by the pan-agonist, WKYMVm. C18 inhibited at the receptor level and blocked WKYMVm signaling through FPR2, resulting in reduced superoxide production and compromised cell chemotaxis. These results identified for the first time that a Ganoderma-derived component with inhibitory effects that acts through a G protein-coupled receptor FPR2. Considering its less than optimal IC50 value, further optimization of C18 would be necessary for future applications.